Artifact Role in Shaping Identity and Empowering Spiritual Practice - Dan Chitoiu; Corina Domnari (Methexis)
Artifacts play an essential role in the contours of a cultural tradition, constituting the constant landmarks of a perennial. Within a given cultural horizon, those artifacts that express the ethos of that horizon in an exemplary way are the most important. In most cases, the artifacts embody symbolic codes and forms belonging to the original, coagulating times of that cultural horizon. Not many artifacts are essential to a cultural pattern, even if they are found on various material supports and configurations. In each culture, particular material supports are favored, and this is an important indication of the landmarks in which a cultural tradition has developed. The reasons why certain artifacts are constantly reproduced, even with certain variations, is a research topic of exceptional importance in understanding the ethos of a culture, a people, or a community. Such an artifact sums up and expresses much more in a symbolic concentration that resonates with the particularities of the material support on which it is found. It is practical wisdom built up over generations, expressed through the genius of the person who decides how to print it on one material support or another.